Betting in sports and Polish criminal law - Leciak, Michał (Studia Iuridica Toruniensia, 2025)
The criminal response to unfair behaviour related to betting in sports is significantly limited in Polish legislation. It only applies to the use of knowledge about acts of corruption within such establishments. Meanwhile, in practice, a number of other activities of perpetrators can be noted, including manipulation of the result or course of sports competition, which are often closely related to participation in the above-mentioned betting. Taking them into account justifies the need for changes in national criminal law solutions.